Molecular characteristic analysis of porcine epidemic diarrhea virus S gene in Zhejiang and surrounding areas - SHAN Ying; LIU Ziqi; SHI Xingfen; LI Guowei; CHEN Cong; LUO Hao; LIU Yajie; FANG Weihuan; LI Xiaoliang (浙江大学学报. 农业与生命科学版, 2018)
We carried out pathogen detection of 282 clinical samples collected from Zhejiang Province and its 24 surrounding areas during April 2013 to April 2017. Among them, 16 positive samples were selected for S gene cloning and sequencing. The results showed that the detection rate of porcine epidemic diarrhea virus (PEDV), porcine group A rotavirus (GARV), porcine deltacoronavirus (PDCoV) and porcine transmissible gastroenteritis virus (TGEV) was 64.89% (183/282), 0.35% (1/282), 4.25% (12/282) and 0% (0/282), respectively. During November 1st to April 1st of the next year, the detection rate of PEDV was 74%, which was 26% in the remaining time. PEDV can be divided into three groups by molecular evolution analysis based on spike (S) protein. All of the 16 positive samples were located in the group Ⅲ. Compared with vaccine strains CV777, SM98, and DR13, the PEDV positive samples shared S gene homology of 93.6%-95.2% in nucleotide identities and 92.4%-94.9% in amino acid identities. Compared with vaccine strain CV777, three additional N- glycosylation sites were formed and one N-glycosylation site was disrupted in the 16 isolated strains. In sum, currently, the main pathogens of piglet diarrhea were PEDV mutants. Prevention and control of porcine epidemic diarrhea should be paid attention to seasonal fluctuations and accelerate the development of epidemic strain vaccine.